Phosphodiesterase-4 Inhibitor Roflumilast-Mediated Protective Effect in Sepsis-Induced Late-Phase Event of Acute Kidney Injury: A Narrative Review - Imran Kazmi; Fahad A. Al-Abbasi; Muhammad Afzal; Muhammad Shahid Nadeem; Hisham N. Altayb; Gaurav Gupta (MDPI AG, 2022)
Severe infections such as viral, bacterial, or fungal sepsis can cause an inflammatory response in the host, leading to organ failure and septic shock-phosphodiesterase-4 (PDE-4) inhibiting related agents from suppressing cyclic adenosine monophosphate (cAMP) degradation. Regulatory organisations have approved some substances in this category to reduce the risk of chronic obstructive pulmonary disease (COPD) exacerbations in patients with chronic bronchitis and a history of COPD exacerbations. Roflumilast has been shown to alleviate inflammatory responses, thus regulating airway inflammation. Additionally, roflumilast therapy dramatically enhanced B-cell lymphoma 2 (Bcl-2) expression, an anti-apoptotic marker lowered in septic animals. Previous research has indicated that roflumilast may help reverse sepsis-induced liver and lung harm, but whether it is also effective in reversing sepsis-induced renal impairment remains unknown. Therefore, this review determines whether roflumilast protects against renal dysfunction, inflammatory response, and apoptosis in sepsis-induced kidney damage. Additionally, we discussed the molecular mechanism through which roflumilast exerts its protective effect to uncover a possible treatment agent for sepsis-induced renal impairment.